Porous composite material and method for manufacturing porous composite material
Patent Information
- Application Number
- JP2025059651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0016】 本発明によれば、低周波数側の吸音性に優れる多孔質複合材料を提供できる。 また、本発明によれば、低周波数側の吸音性に優れる多孔質複合材料の製造方法を提供できる。
Smart Images

Figure 2026166604000001
Abstract
Description
[Technical Field]
[0001] This invention relates to porous composite materials and methods for producing porous composite materials. [Background technology]
[0002] Traditionally, metal plates such as lead and iron have been used as sound insulation and sound absorption materials. However, because metal plates are heavy, the development of lightweight sound insulation and sound absorption materials is progressing.
[0003] For example, Patent Document 1 discloses a porous body that is lightweight and has excellent sound insulation properties, having continuous pores and a first surface and a second surface on the opposite side of the first surface, wherein the porous body contains a plurality of particles, and the concentration of particles on the second surface side is three times or more than the concentration of particles on the first surface side. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2019-167388 [Overview of the project] [Problems that the invention aims to solve]
[0005] Incidentally, in recent years, the development of electric vehicles (EVs) has been progressing. One of the characteristics of EVs is that they are quiet because they do not have an engine and therefore do not produce engine noise.
[0006] Previously, engine noise (around 200-10,000 Hz) transmitted into the car's interior meant that relatively low-frequency sounds such as road noise (around 100-1,000 Hz) generated from tire contact with the ground while driving, and wind noise (around 900-10,000 Hz) were not noticeable. However, with EVs being quieter, a new problem has arisen: these low-frequency sounds have become more noticeable. Therefore, it has become necessary to reduce these low-frequency sounds.
[0007] However, conventional sound insulation and sound absorption materials are insufficient in reducing the low-frequency sounds described above, and this needed to be improved.
[0008] Therefore, the present invention aims to provide a porous composite material that exhibits excellent sound absorption on the low-frequency side. Furthermore, the present invention aims to provide a method for manufacturing a porous composite material that exhibits excellent sound absorption on the low-frequency side. [Means for solving the problem]
[0009] The inventors diligently conducted research with the aim of solving the above problems. As a result, the inventors newly discovered that the above problems can be solved if the porous composite material contains silica xerogel and porous resin, and the average pore size obtained by the mercury intrusion method and the average pore size obtained by the BJH method (Barrett-Joyner-Halenda method) are both within a predetermined range, and thus completed the present invention.
[0010] In other words, the present invention aims to advantageously solve the above problems, [1] and the present invention is a porous composite material comprising silica xerogel and porous resin, wherein the silica xerogel contains polysiloxane particles, the average pore size A obtained by the mercury intrusion method is 5.0 μm or more and 35.0 μm or less, and the average pore size B obtained by the BJH method is 5.0 nm or more and 30.0 nm or less. The porous composite materials described above exhibit excellent sound absorption at low frequencies. Here, "xerogel" refers to "a gel consisting of an open network formed by removing a swelling agent from a gel," according to the "Definitions of Terms relating to the Structure and Process of Sols, Gels, Meshes, and Inorganic-Organic Composite Materials (IUPAC Recommendation 2007)" by the Subcommittee on Polymer Terminology of the Inorganic Chemistry and Polymer Divisions of the International Union of Pure and Applied Chemistry (IUPAC). Although there is a classification method that defines aerogels as those obtained by removing the swelling agent (solvent) by supercritical drying, xerogels as those obtained by removing the swelling agent (solvent) by normal evaporation drying, and cryogels as those obtained by freeze-drying, in this specification, these will all be collectively referred to as "xerogels." In this specification, the average pore diameter A measured by the mercury intrusion method is the average pore diameter measured by the mercury intrusion method, and can be measured according to the method described in the examples of this specification. In this specification, the average pore size B by the BJH method is the average pore size of mesopores (3.4 nm to 200 nm) in a porous composite material measured by the BJH method in the nitrogen adsorption method, and can be measured according to the method described in the examples of this specification.
[0011] [2] In the porous composite material described in [1] above, the porous resin has a contiguous pore structure, the silica xerogel has a structure in which the polysiloxane particles are linked together in a pearl necklace-like manner, and it is preferable that the silica xerogel is present in the contiguous pores of the porous resin. If the porous resin and the silica xerogel each have the above-described structure, and the silica xerogel is present in the interconnected pores of the porous resin, the sound absorption properties on the low-frequency side of the porous composite material can be improved. In this specification, "pearl necklace-like" means that the polysiloxane particles are linked together in a three-dimensional manner, forming a shape similar to a pearl necklace. In this specification, "connecting pore structure" refers to a structure that constitutes a part of a porous resin, in which multiple fine pores are formed from the surface toward the interior of the porous composite material, and these multiple pores do not exist independently of each other, but are interconnected (connected) to one another.
[0012] [3] In the porous composite material according to the above [1] or [2], the surface of the polysiloxane particles is preferably hydrophobized. When the surfaces of the polysiloxane particles are hydrophobized, the sound absorption property of the porous composite material on the low frequency side can be improved.
[0013] [4] In the porous composite material according to any one of the above [1] to [3], the content ratio of the polysiloxane particles in the porous composite material is preferably 50 mass% or more and 85 mass% or less. When the content ratio of the polysiloxane particles in the porous composite material is not less than the above lower limit, the sound absorption property of the porous composite material on the low frequency side can be effectively improved. On the other hand, when the content ratio of the polysiloxane particles in the porous composite material is not more than the above upper limit, the weight of the porous composite material can be effectively reduced. In the present specification, the content ratio of the polysiloxane particles in the porous composite material can be measured according to the method described in the Examples of the present specification.
[0014] [5] In the porous composite material according to any one of the above [1] to [4], the porous resin is preferably composed of a poly(meth)acrylic acid alkyl ester or a nitrile group-containing polymer. When the porous resin is composed of a poly(meth)acrylic acid alkyl ester or a nitrile group-containing polymer, a porous composite material having excellent sound absorption properties on the low frequency side can be efficiently obtained. In the present specification, "poly(meth)acrylic" means polyacrylic and / or polymethacrylic.
[0015] Furthermore, the present invention aims to advantageously solve the above problems, [6] The present invention is a method for producing a porous composite material comprising silica xerogel and porous resin, comprising: a preparation step of preparing a homogeneous phase comprising an organic solvent, a polysiloxane precursor, an organic polymer, and water; a precipitate formation step of subjecting the homogeneous phase to a condensation hydrophobicization step of condensing part or all of the polysiloxane precursor to form polysiloxane particles and hydrophobicizing the surface of the polysiloxane particles, and a precipitation step of precipitating the organic polymer by a phase separation method to obtain a porous resin, thereby obtaining a precipitate comprising the polysiloxane particles and the porous resin; and a drying step of drying the precipitate. Using the above-described method for manufacturing porous composite materials, it is possible to obtain porous composite materials that exhibit excellent sound absorption at low frequencies. [Effects of the Invention]
[0016] According to the present invention, a porous composite material with excellent sound absorption properties on the low-frequency side can be provided. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a porous composite material that exhibits excellent sound absorption on the low-frequency side. [Modes for carrying out the invention]
[0017] Embodiments of the present invention will be described in detail below.
[0018] (Porous composite material) The porous composite material of the present invention comprises a silica xerogel and a porous resin, wherein the silica xerogel contains polysiloxane particles. The porous composite material of the present invention has an average pore size A (hereinafter sometimes simply referred to as "average pore size A") of 5 μm to 35 μm, determined by the mercury intrusion method, and an average pore size B (hereinafter sometimes simply referred to as "average pore size B") of 5 nm to 30 nm, determined by the BJH method. The porous composite material described above exhibits excellent sound absorption on the low-frequency side. This is presumed to be because the porous composite material contains pores in which the average pore diameter A and average pore diameter B are within predetermined ranges, thereby making it a porous composite material capable of effectively absorbing low-frequency sounds. Furthermore, it is presumed that the inclusion of silica xerogel containing polysiloxane particles in the porous composite material allowed the average pore diameter B to be adjusted to the predetermined range. Furthermore, because the porous composite material of the present invention exhibits excellent sound absorption on the low-frequency side, it can be suitably used as a sound-absorbing material, particularly a sound-absorbing material that absorbs road noise and wind noise. In other words, the porous composite material of the present invention may also be a sound-absorbing material. Furthermore, the porous composite material of the present invention can be obtained by the method for producing the porous composite material of the present invention, which will be described later.
[0019] In the porous composite material of the present invention, the porous resin has a interconnected pore structure, and the silica xerogel has a structure in which polysiloxane particles are linked together in a pearl necklace-like manner, and it is preferable that the silica xerogel is present in the interconnected pores of the porous resin. If the porous resin and the silica xerogel each have the above-described structure, and the silica xerogel is present in the interconnected pores of the porous resin, the sound absorption properties on the low-frequency side of the porous composite material can be improved.
[0020] The porous composite material of the present invention may optionally contain components other than the silica xerogel and porous resin described above (hereinafter sometimes referred to as "other components"). Other components include, for example, hydrophobic agents that can be used in the method for producing the porous composite material of the present invention, which will be described later.
[0021] <Porous resin> The organic polymer constituting the porous resin is not particularly limited, but examples include poly(meth)acrylate alkyl esters such as methyl polyacrylate, ethyl polyacrylate, polymethyl methacrylate, and polyethyl methacrylate; nitrile group-containing polymers such as polyacrylonitrile and polymethacrylonitrile; polylactide; lactide-ε-caprolactone copolymer, etc. These may be used individually or two or more may be combined in any proportion. Among these, the organic polymer is preferably poly(meth)acrylate alkyl ester or nitrile group-containing polymer, and more preferably poly(meth)acrylate alkyl ester, because it is possible to efficiently obtain a porous composite material with excellent sound absorption on the low-frequency side. As the poly(meth)acrylate alkyl ester, polymethyl methacrylate is preferred, and as the nitrile group-containing polymer, acrylonitrile is preferred.
[0022] The content of porous resin in the porous composite material is preferably 15% by mass or more, more preferably 25% by mass or more, even more preferably 35% by mass or more, preferably 90% by mass or less, more preferably 75% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less. If the content ratio of porous resin in the porous composite material is above the lower limit mentioned above, the porous composite material can be effectively made lighter. On the other hand, if the proportion of polysiloxane particles in the porous composite material is below the above upper limit, the sound absorption properties on the low-frequency side of the porous composite material can be effectively improved.
[0023] <Silica Xerogel> Silica xerogel contains polysiloxane particles. The polysiloxane particles contained in silica xerogel can be condensed polysiloxane precursors (condensates). Examples of polysiloxane precursors include alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; oligomers obtained by partially hydrolyzing alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; and organoalkoxysilane compounds such as methyltrimethoxysilane and phenyltrimexysilane. These may be used individually or in combination of two or more in any proportion. Among those listed above, alkoxysilane compounds are preferred as polysiloxane precursors, and tetramethoxysilane is more preferred. That is, polysiloxane particles are preferably composed of condensates of alkoxysilane compounds, and more preferably composed of condensates of tetramethoxysilane.
[0024] Here, it is preferable that the surface of the polysiloxane particles is hydrophobic. If the surface of the polysiloxane particles is hydrophobic, the polysiloxane particles attract moisture, and the risk of pore collapse due to surface tension and other factors when this moisture evaporates can be effectively suppressed. As a result, the risk of a decrease in the sound absorption properties of the porous composite material can be effectively suppressed. In addition, if the surface of the polysiloxane particles is hydrophobic, the average pore size A and / or average pore size B can be easily adjusted. Furthermore, a hydrophobic agent can be used to hydrophobize the surface of polysiloxane particles. Examples of hydrophobic agents include those that can be used in the method for producing the porous composite material of the present invention, which will be described later.
[0025] The content of polysiloxane particles in the porous composite material is preferably 10% by mass or more, more preferably 25% by mass or more, even more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, preferably 85% by mass or less, more preferably 75% by mass or less, and even more preferably 65% by mass or less. If the proportion of polysiloxane particles in the porous composite material is above the lower limit mentioned above, the sound absorption properties of the porous composite material on the low-frequency side can be effectively improved. On the other hand, if the proportion of polysiloxane particles in the porous composite material is below the above upper limit, the porous composite material can be effectively made lighter.
[0026] <Other ingredients> The porous composite material of the present invention may contain other components such as hydrophobic agents, but the content of these components is preferably 5% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0% by mass. In other words, it is even more preferable that the porous composite material does not contain other components.
[0027] <Properties of porous composite materials> The average pore size A of the porous composite material must be 5.0 μm or more, preferably 8.0 μm or more, more preferably 12.0 μm or more, must be 35.0 μm or less, preferably 25.0 μm or less, more preferably 18.0 μm or less, and even more preferably 14.0 μm or less. If the average pore size A of the porous composite material is greater than or equal to the lower limit mentioned above, silica xerogel can be effectively contained within the voids (pores) of the porous resin. On the other hand, if the average pore size A of the porous composite material is below the above upper limit, the sound absorption properties on the low-frequency side of the porous composite material can be effectively improved. The average pore size A of the porous composite material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous composite material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on.
[0028] The average pore size B of the porous composite material must be 5.0 nm or larger, preferably 9.0 nm or larger, more preferably 11.0 nm or larger, even more preferably 13.0 nm or larger, and must be 30.0 nm or smaller, preferably 20.0 nm or smaller, and more preferably 15.0 nm or smaller. If the average pore size B of the porous composite material is within the above range, the sound absorption properties on the low-frequency side of the porous composite material can be effectively improved. The average pore size B of the porous composite material can be adjusted, for example, by the conditions of each step in the manufacturing method of the porous composite material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on.
[0029] The ratio of average pore diameter B to average pore diameter A (average pore diameter B / average pore diameter A) is preferably 0.10 [nm / μm] or more, more preferably 0.30 [nm / μm] or more, even more preferably 0.60 [nm / μm] or more, even more preferably 0.90 [nm / μm] or more, preferably 7.00 [nm / μm] or less, more preferably 5.00 [nm / μm] or less, even more preferably 3.00 [nm / μm] or less, and even more preferably 1.50 [nm / μm] or less. If the ratio of average pore diameter B to average pore diameter A is within the above range, the sound absorption properties on the low-frequency side of the porous composite material can be effectively improved.
[0030] The specific surface area A of porous composite materials obtained by the mercury intrusion method (hereinafter sometimes simply referred to as "specific surface area A") is 50 m². 2 It is preferable that it be 100m or more per gram. 2 It is more preferable that it be 110m or more per gram. 2 It is even more preferable that it be 120m or more / g. 2 It is even more preferable that it be 300m or more per gram. 2 It is preferable that it be less than / g, and 200m 2 It is more preferable that it be less than or equal to / g, and 150m 2 / g or less is even more preferable. When the specific surface area A of the porous composite material is at least the above lower limit, the sound absorbency of the porous composite material on the low frequency side can be effectively improved. On the other hand, when the specific surface area A of the porous composite material is at most the above upper limit, the silica xerogel can be effectively accommodated in the voids (pores) of the porous resin. The specific surface area A of the porous composite material can be adjusted, for example, by the conditions of each step of the method for producing the porous composite material of the present invention described later, in particular, the usage amounts and ratios of raw materials, the conditions for condensing polysiloxane particles, the conditions for precipitating the organic polymer, and the like. In the present specification, the specific surface area A by the mercury intrusion method is the specific surface area measured by the mercury intrusion method, and can be measured according to the method described in the Examples of the present specification.
[0031] The specific surface area B of the porous composite material measured by the BET method (Brunauer-Emmett-Teller method) (hereinafter sometimes simply referred to as "specific surface area B") is 100 m 2 / g or more is preferable, 200 m 2 / g or more is more preferable, 240 m 2 / g or more is even more preferable, and 260 m 2 / g or more is still even more preferable. When the specific surface area B of the porous composite material is at least the above lower limit, the sound absorbency of the porous composite material on the low frequency side can be effectively improved. The specific surface area B is, for example, 500 m 2 / g or less, may be 400 m 2 / g or less, or may be 300 m 2 / g or less. The specific surface area B of the porous composite material can be adjusted, for example, by the conditions of each step of the method for producing the porous composite material of the present invention described later, in particular, the usage amounts and ratios of raw materials, the conditions for condensing polysiloxane particles, the conditions for precipitating the organic polymer, and the like. In the present specification, the specific surface area B by the BET method is the specific surface area measured by the BET method in the nitrogen adsorption method, and can be measured according to the method described in the Examples of the present specification.
[0032] The ratio of specific surface area B to specific surface area A (specific surface area B / specific surface area A) is preferably 0.50 or more, more preferably 1.00 or more, even more preferably 2.00 or more, preferably 4.00 or less, more preferably 2.50 or less, even more preferably 2.16 or less, and even more preferably 2.14 or less. If the ratio of specific surface area B to specific surface area A is within the above range, the sound absorption properties on the low-frequency side of the porous composite material can be effectively improved.
[0033] The apparent density of the porous composite material is 0.050 g / cm³. 3 Preferably, it should be 0.100 g / cm³ or more. 3 It is more preferable that the amount be greater than or equal to 0.150 g / cm³. 3 It is even more preferable that the amount be greater than or equal to 0.200 g / cm³. 3 It is even more preferable that the amount be greater than or equal to 0.220 g / cm³. 3 It is even more preferable that the above is true, specifically 0.700 g / cm³. 3 Preferably, it is 0.500 g / cm³. 3 It is more preferable that the following is the case: 0.300 g / cm³ 3 It is even more preferable that the following is the case: 0.250 g / cm³ 3 The following is even more preferable: If the apparent density of the porous composite material is above the lower limit mentioned above, it can possess a certain level of strength, and as a result, it can become a porous composite material with excellent processability. On the other hand, if the apparent density of the porous composite material is below the above upper limit, the sound absorption properties of the porous composite material can be improved overall. The apparent density of the porous composite material can be adjusted, for example, by the conditions of each step in the method for producing the porous composite material of the present invention, as described later, particularly by the amount and ratio of raw materials used, the conditions for condensing polysiloxane particles, the conditions for precipitating organic polymers, and so on. In this specification, the apparent density of a porous composite material can be measured according to the methods described in the examples of this specification.
[0034] (Method for manufacturing porous composite materials) The present invention relates to a method for producing a porous composite material (hereinafter sometimes simply referred to as "the production method"), which is a method for producing a porous composite material comprising silica xerogel and a porous resin, and comprises a preparation step of preparing a homogeneous phase comprising an organic solvent, a polysiloxane precursor, an organic polymer, and water; a precipitate formation step of subjecting the homogeneous phase to a condensation hydrophobicization step in which part or all of the polysiloxane precursor is condensed to form polysiloxane particles and the surface of the polysiloxane particles is made hydrophobic, and a precipitation step in which the organic polymer is precipitated by a phase separation method to obtain a porous resin, thereby obtaining a precipitate comprising polysiloxane particles and a porous resin; and a drying step of drying the precipitate. Using the manufacturing method described above, a porous composite material with excellent sound absorption on the low-frequency side can be obtained. This is presumed to be because, by precipitating a precipitate containing polysiloxane particles and porous resin from a homogeneous phase using a predetermined method, and then drying this precipitate, the average pore size A and average pore size B of the resulting porous composite material fall within predetermined ranges. Furthermore, the porous composite material obtained by the above manufacturing method can effectively maintain its shape because the silica xerogel and porous resin are intricately intertwined within the porous composite material. Furthermore, the porous composite material of the present invention described above can be obtained by using the manufacturing method described above.
[0035] In addition to the preparation step, precipitate formation step, and drying step described above, the manufacturing method of the present invention may optionally include a washing step in which the precipitate obtained in the precipitate formation step is washed with a washing solvent, and a solvent replacement step in which the solvent, such as the washing solvent, contained in the precipitate after the washing step is replaced with another solvent (hereinafter sometimes referred to as "replacement solvent").
[0036] <Preparation process> In the preparation step, a homogeneous phase is prepared containing an organic solvent, a polysiloxane precursor, an organic polymer, and water. Optionally, components other than the organic solvent, polysiloxane precursor, organic polymer, and water may be added to the homogeneous phase.
[0037] The method for preparing the homogeneous phase is not particularly limited, and examples include (1) a method of preparing the homogeneous phase by mixing each component in any order, (2) a method of preparing an aqueous solution containing an organic solvent first, adding the polysiloxane precursor and the organic polymer to the aqueous solution, and dissolving them together to prepare the homogeneous phase, and (3) a method of preparing an aqueous solution containing an organic solvent first, dissolving one of the polysiloxane precursor and the organic polymer in the aqueous solution, and then dissolving the other to prepare the homogeneous phase. Among these, method (3) is preferred because it allows for efficient acquisition of the homogeneous phase, and it is more preferable to prepare an aqueous solution containing an organic solvent, dissolve the organic polymer in the aqueous solution, and then dissolve the polysiloxane precursor.
[0038] The dissolution temperature of the polysiloxane precursor and organic polymer when preparing the above-mentioned homogeneous phase is not particularly limited as long as it is a temperature at which the homogeneous phase can be maintained, but it is preferably 40°C or higher, more preferably 55°C or higher, preferably 100°C or lower, and more preferably 90°C or lower. If the melting temperature is within the above range, porous composite materials can be obtained more easily.
[0039] <<Polysiloxane precursor>> The polysiloxane precursor is not particularly limited as long as it forms polysiloxane particles and yields a homogeneous phase, but examples include alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; oligomers obtained by partially hydrolyzing alkoxysilane compounds such as tetramethoxysilane and tetraethoxysilane; and organoalkoxysilane compounds such as methyltrimethoxysilane and phenyltrimexysilane. These may be used individually or in combination of two or more in any proportion. Among these, alkoxysilane compounds are preferred as the polysiloxane precursor because porous composite materials can be obtained more easily, and tetramethoxysilane is more preferred.
[0040] The content of the polysiloxane precursor in the homogeneous phase is preferably 4.0% by mass or more, more preferably 10.0% by mass or more, even more preferably 14.0% by mass or more, even more preferably 18.0% by mass or more, preferably 40.0% by mass or less, more preferably 30.0% by mass or less, and even more preferably 25.0% by mass or less. If the content of the polysiloxane precursor in the homogeneous phase is above the lower limit mentioned above, the condensation of the polysiloxane precursor can be carried out efficiently in the condensation process. Furthermore, the sound absorption properties on the low-frequency side of the resulting porous composite material can be effectively improved. On the other hand, if the proportion of polysiloxane precursor in the homogeneous phase is below the above upper limit, manufacturing costs can be effectively reduced.
[0041] <<Organic Polymers>> The organic polymer is not particularly limited as long as it forms a porous resin and yields a homogeneous phase, but examples include poly(meth)acrylate alkyl esters such as methyl polyacrylate, ethyl polyacrylate, polymethyl methacrylate, and polyethyl methacrylate; nitrile group-containing polymers such as polyacrylonitrile and polymethacrylonitrile; polylactide; and lactide-ε-caprolactone copolymer. These may be used individually or in any combination of two or more in any proportion. Among these, the organic polymer is preferably a poly(meth)acrylate alkyl ester or a nitrile group-containing polymer, and more preferably a poly(meth)acrylate alkyl ester. Polymethyl methacrylate is preferred as the poly(meth)acrylate alkyl ester, and acrylonitrile is preferred as the nitrile group-containing polymer.
[0042] The content of the organic polymer in the homogeneous phase is preferably 1.0% by mass or more, more preferably 4.0% by mass or more, particularly preferably 6.0% by mass or more, preferably 30.0% by mass or less, more preferably 20.0% by mass or less, even more preferably 10.0% by mass or less, even more preferably 9.5% by mass or less, and even more preferably 9.0% by mass or less. If the content of the organic polymer in the homogeneous phase is above the lower limit mentioned above, the organic polymer can be efficiently precipitated in the precipitation process. On the other hand, if the proportion of organic polymer in the homogeneous phase is below the above upper limit, the organic polymer becomes more easily soluble in organic solvents, and the manufacturing process can be made more efficient. In addition, the sound absorption properties on the low-frequency side of the resulting porous composite material can be effectively improved.
[0043] Here, the mass ratio of the organic polymer to the polysiloxane precursor in the homogeneous phase (organic polymer / polysiloxane precursor) is preferably 0.10 or higher, more preferably 0.20 or higher, even more preferably 0.40 or higher, preferably 2.00 or lower, more preferably 1.00 or lower, even more preferably 0.70 or lower, and even more preferably 0.50 or lower. If the mass ratio of the organic polymer to the polysiloxane precursor is above the lower limit mentioned above, the sound absorption properties on the low-frequency side of the resulting porous composite material can be effectively improved. On the other hand, if the mass ratio of the organic polymer to the polysiloxane precursor is below the above upper limit, the strength of the porous composite material can be effectively improved.
[0044] <<Organic solvent>> The organic solvent is not particularly limited as long as it can produce a homogeneous phase, but examples include alcohols such as methanol and ethanol; sulfur-containing solvents such as dimethyl sulfoxide and sulfolane; ketones such as acetone and methyl ethyl ketone; and tetrahydrofuran. These may be used individually or in combination of two or more in any proportion. The organic solvent is preferably an alcohol or a sulfur-containing solvent. Ethanol is preferred as the alcohol, and dimethyl sulfoxide is preferred as the sulfur-containing solvent.
[0045] The content of the organic solvent in the homogeneous phase is preferably 20.0% by mass or more, more preferably 40.0% by mass or more, even more preferably 60.0% by mass or more, preferably 95.0% by mass or less, more preferably 85.0% by mass or less, even more preferably 75.0% by mass or less, and even more preferably 72.0% by mass or less. If the proportion of organic solvent in the homogeneous phase is above the lower limit mentioned above, the organic polymer can be efficiently dissolved. On the other hand, if the proportion of organic solvent in the homogeneous phase is below the above upper limit, the precipitation of the organic polymer in the precipitation process will be accelerated, effectively improving productivity. Furthermore, the sound absorption properties on the low-frequency side of the resulting porous composite material can be effectively improved.
[0046] <<Solid content concentration of homogeneous phase>> The solid content concentration of the homogeneous phase is preferably 5.0% by mass or more, more preferably 8.0% by mass or more, even more preferably 20.0% by mass or more, even more preferably 25.0% by mass or more, even more preferably 28.0% by mass or more, preferably 60.0% by mass or less, and even more preferably 40.0% by mass or less.
[0047] <Precipitate formation process> In the precipitate formation process, the homogeneous phase prepared in the preparation process is used. A condensation hydrophobicization step involves condensing part or all of a polysiloxane precursor to form polysiloxane particles and hydrophobicizing the surface of the polysiloxane particles, and Precipitation process to obtain porous resin by precipitating organic polymers using a phase separation method. By applying this method, a precipitate containing polysiloxane particles and porous resin is obtained. The precipitate obtained by the above precipitate formation process has the desired porous state internally and maintains that porous state. Therefore, it can be dried without supercritical drying in the subsequent drying process.
[0048] In this context, the order in which the homogeneous phase prepared in the preparation step is subjected to the condensation hydrophobicization step and the precipitation step in the precipitate formation step is not particularly limited. In the precipitate formation process, the condensation hydrophobication process may be performed before the precipitation process, the precipitation process may be performed before the condensation hydrophobication process, or the condensation hydrophobication process and the precipitation process may be performed simultaneously. However, it is preferable to perform the condensation hydrophobication process before the precipitation process because it is easier to obtain porous composite materials.
[0049] In the following, the precipitate formation process will be explained using a precipitate formation process in which a condensation hydrophobicization process is performed followed by a precipitation process as an example; however, the precipitate formation process in the manufacturing method of the present invention is not limited to this.
[0050] <<Condensation Hydrophobicization Process>> In the condensation hydrophobicization process, part or all of the polysiloxane precursor is condensed to form polysiloxane particles (condensation process), and the surface of the polysiloxane particles is made hydrophobic (hydrophobicization process). The condensation hydrophobicization step may optionally include a gel formation step between the condensation step and the hydrophobicization step, in which the solution after the condensation step is left for a predetermined time to obtain a wet gel, and a crushing step in which the gel obtained in the gel formation step is crushed.
[0051] [Condensation step] In the condensation process, some or all of the polysiloxane precursor is condensed to form polysiloxane particles.
[0052] The condensation of polysiloxane precursors is not particularly limited as long as polysiloxane particles can be obtained, but it can be carried out by adding a catalyst to a homogeneous phase. Examples of catalysts include base catalysts such as aqueous ammonia, urea, and amines; and acid catalysts such as hydrochloric acid, acetic acid, and oxalic acid. These may be used individually or in any combination of two or more in any proportion. Among these, base catalysts are preferred, and aqueous ammonia is more preferred.
[0053] The amount of catalyst added to the homogeneous phase is preferably 0.05 mmol or more, more preferably 0.01 mmol or more, more preferably 0.3 mmol or less, and more preferably 0.2 mmol or less, per mole of polysiloxane precursor.
[0054] The condensation time of the polysiloxane precursor is preferably 1 minute or more, more preferably 5 minutes or more, preferably 20 minutes or less, and more preferably 15 minutes or less. If the condensation time of the polysiloxane precursor is above the lower limit mentioned above, the amount of unreacted polysiloxane precursor can be effectively suppressed. On the other hand, if the condensation time of the polysiloxane precursor is below the above upper limit, the productivity of porous composite materials can be effectively improved. The condensation time mentioned above refers to the time from the completion of catalyst addition to the homogeneous phase until the formation of the gel body, described later, begins, or the time until the hydrophobicization process, described later, begins.
[0055] The condensation temperature of polysiloxane precursors is typically between 23°C and 80°C.
[0056] [Gel formation process] In any gel formation step, the solution after the condensation step is left to stand for a predetermined time to obtain a wet gel. By including a gel formation step in the condensation and hydrophobicization process, the polysiloxane precursor can be sufficiently condensed to efficiently obtain polysiloxane particles.
[0057] The standing time in the gel formation process is preferably 0.1 hours or more, more preferably 0.5 hours or more, preferably 24 hours or less, and more preferably 12 hours or less. If the standing time during the gel formation process is above the lower limit mentioned above, the amount of unreacted polysiloxane precursor can be effectively suppressed. On the other hand, if the standing time in the gel formation process is below the above upper limit, the productivity of porous composite materials can be effectively improved. The above-mentioned standing time refers to the time from when the formation of the gel body begins until the start of any of the disintegration steps described later, or until the start of the hydrophobicization step described later.
[0058] The standing temperature during the gel formation process is typically between 23°C and 80°C.
[0059] [Crushing process] In any disintegration step, the gel obtained in the gel formation step is disintegrated. By including a crushing step in the condensation hydrophobicization process, the hydrophobicization process can be carried out more efficiently. The disintegration of the gel is not particularly limited and may be done automatically using a stirrer or by hand using a rod or the like.
[0060] In the crushing step, the viscosity may be adjusted by adding the aforementioned organic solvent or aqueous solution containing an organic solvent to the gel. This allows the gel to be crushed efficiently. The amount of organic solvent or aqueous solution containing an organic solvent used can be adjusted as appropriate to the desired viscosity.
[0061] In the crushing process, the gel may be heated to suppress the precipitation of organic polymers. This allows for efficient crushing of the gel. The heating temperature is not particularly limited as long as it can suppress the precipitation of the organic polymer, but it is preferably 40°C or higher, preferably 50°C or higher, preferably 70°C or lower, and more preferably 65°C or lower.
[0062] [Hydrophobicization process] In the hydrophobicization process, the surface of the polysiloxane particles is made hydrophobic. By making the surface of the polysiloxane particles hydrophobic, the risk of pore collapse due to surface tension and other factors when moisture attracted to the polysiloxane particles evaporates during the drying process described later can be effectively suppressed, and as a result, the risk of a decrease in the sound absorption properties of the resulting porous composite material can be effectively suppressed. In addition, by making the surface of the polysiloxane particles hydrophobic, the average pore size A and / or average pore size B can be easily adjusted. In addition, hydrophobic agents are typically used to hydrophobize the surface of polysiloxane particles.
[0063] Alkoxyalkylsilanes can be used as hydrophobic agents in the hydrophobication process. Examples of alkoxyalkylsilanes include monoalkoxytrialkylsilanes, dialoxydialkylsilanes, and trialkoxymonoalkylsilanes. Among these, trialkoxymonoalkylsilanes are preferred. Examples of trialkoxy monoalkylsilanes include trimethoxymethylsilane, trimethoxypropylsilane, trimethoxyhexylsilane, trimethoxydecylsilane, triethoxymethylsilane, and triethoxypropylsilane. Among these, trimethoxymethylsilane is preferred. The items listed above may be used individually or in any combination of two or more items in any proportion.
[0064] The mass ratio of the hydrophobic agent to the polysiloxane precursor used in the above preparation step (hydrophobic agent / polysiloxane precursor) is preferably 0.1 or higher, more preferably 0.3 or higher, even more preferably 0.5 or higher, preferably 5.0 or lower, more preferably 2.0 or lower, and even more preferably 1.0 or lower. If the mass ratio of the hydrophobic agent to the polysiloxane precursor is above the lower limit mentioned above, the sound absorption properties on the low-frequency side of the resulting porous composite material can be effectively improved.
[0065] <<Precipitation process>> In the precipitation process, an organic polymer is precipitated by a phase separation method to obtain a porous resin. If the precipitate formation step involves a condensation hydrophobicization step followed by a precipitation step, the precipitation step can yield a precipitate containing polysiloxane particles and porous resin. This precipitate is typically in a wet state.
[0066] In the precipitation process, the phase separation method is not particularly limited as long as it allows for the precipitation of the organic polymer to obtain a porous resin. However, a thermal-induced phase separation method is preferred, i.e., a method in which a solution or gel containing the organic polymer is cooled to precipitate the porous resin, as this makes it easier to obtain porous composite materials.
[0067] When using the thermally induced phase separation method in the precipitation process, the cooling temperature is not particularly limited as long as it is below the crystallization temperature (crystalline polymer) or glass transition temperature (amorphous polymer) of the organic polymer, as it is the cooling temperature at which the structure of the porous resin solidifies. However, it is preferably -40°C or higher, more preferably -30°C or higher, preferably 0°C or lower, and even more preferably -10°C or lower. If the cooling temperature is above the lower limit mentioned above, the freezing of organic solvents and water can be suppressed, effectively improving the productivity of porous composite materials. On the other hand, if the cooling temperature is below the above upper limit, the porous resin can be efficiently precipitated.
[0068] When using the thermally induced phase separation method in the precipitation process, the cooling time is usually between 5 minutes and 3 hours.
[0069] <Washing process> In any washing step, the precipitate obtained in the precipitate formation step is washed with a washing solvent. This effectively removes unreacted polysiloxane precursors, hydrophobic agents, and other impurities.
[0070] As a cleaning solvent, a solvent that is a poor solvent for porous resins and a good solvent for water can be used. For example, the solvents listed in the "organic solvents" section above can be used.
[0071] The temperature of the washing solvent used when washing precipitates is typically between -40°C and 0°C.
[0072] <Solvent replacement process> In the optional solvent replacement step, the solvent, such as the washing solvent, contained in the precipitate after the washing step is replaced with a replacement solvent. This allows for efficient drying of the precipitate in the drying step described later. Furthermore, it effectively suppresses damage to the precipitate, such as cracking.
[0073] As the substitution solvent, a solvent that is a poor solvent for porous resins and has a lower surface tension than the washing solvent can be used. For example, alkanes such as n-hexane and n-heptane can be used. Among these, n-heptane is preferred.
[0074] <Drying process> In the drying step, the precipitate obtained in the precipitate formation step, optional washing step, or optional solvent substitution step is dried. In the manufacturing method of the present invention, the interior of the precipitate is in the desired porous state, and it is possible to dry it while maintaining the porous state, so drying can be done without supercritical drying. For this reason, supercritical drying is not usually performed in the drying step of the manufacturing method of the present invention.
[0075] The drying temperature of the precipitate is not particularly limited as long as the solvent contained in the precipitate (organic solvent, water, washing solvent, substitution solvent, etc.) can be removed, but it is usually between 20°C and 40°C.
[0076] The drying time for the precipitate is not particularly limited as long as the solvent contained in the precipitate can be removed, but it is usually between 2 and 24 hours. [Examples]
[0077] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the examples and comparative examples, the polysiloxane particle content, apparent density, average pore size A and specific surface area A by mercury intrusion method, specific surface area B by BET method, average pore size B by BJT method, and maximum sound absorption coefficient on the low-frequency side were measured using the following procedure.
[0078] <Polysiloxane particle content> The polysiloxane particle content of the porous composite materials obtained in the examples and comparative examples was measured using a differential scanning calorimetry analyzer (STA7200, Hitachi High-Tech Science). Specifically, samples cut from porous composite material were placed in an aluminum container designed for the apparatus, and heated to 500°C under conditions of a nitrogen gas flow rate of 20 mL / min and a temperature of 20°C / min to obtain a TG curve. Using the analysis software provided with the apparatus, the residual weight percentage at 500°C was calculated, and this calculated value was taken as the content ratio of polysiloxane particles.
[0079] <Apparent Density> The mass of the porous composite material obtained in the examples and comparative examples was measured using an electronic balance, and the apparent density (m³) of the porous composite material was calculated by dividing the mass by the volume of the porous composite material. 2 We calculated / g).
[0080] <Average pore size A and specific surface area A by mercury intrusion method> The average pore size A of the porous composite material was determined by mercury intrusion using a mercury porosimeter (Autopore V9620, Micromeritix). In the mercury intrusion measurement using a mercury porosimeter, the pore size is determined by modeling the pores as cylindrical and using Washburn's equation (-4σcosθ=PD [wherein σ represents the surface tension of mercury (N / m), θ represents the contact angle (deg), D represents the diameter of the pore (m), and P represents the pressure (Pa)]). Specifically, the porous composite materials obtained in Examples and Comparative Examples were vacuum-dried at 80°C for 8 hours, and measurements were performed under the following conditions. The pore diameter at which the cumulative pore volume reached 50% of the total pore volume was defined as the average pore diameter A of the porous composite material. Further, the specific surface area A of the porous composite material was determined from the obtained value of the cumulative pore volume. Measurement range: φ0.0036 μm to 200 μm Mercury contact angle: 140° Mercury surface tension: 480 dynes / cm (0.480 N / m)
[0081] <Specific Surface Area B by BET Method> Using a specific surface area measuring apparatus (manufactured by MicrotracBEL Corp., BELSORP-miniII), nitrogen gas was adsorbed onto the porous composite materials obtained in Examples and Comparative Examples, and the specific surface area B of each porous composite material was measured by the BET method in the nitrogen adsorption process.
[0082] <Average Pore Diameter B by BJH Method> Using a specific surface area measuring apparatus (manufactured by MicrotracBEL Corp., BELSORP-miniII), nitrogen gas was adsorbed onto the porous composite materials obtained in Examples and Comparative Examples, and the average pore diameter B of each porous composite material was measured by the BJH method in the nitrogen adsorption process. Specifically, a nitrogen adsorption isotherm was measured by adsorbing nitrogen gas onto the porous composite materials obtained in Examples and Comparative Examples, a BJH plot was calculated from the nitrogen adsorption isotherm, then the pore diameter peak on the adsorption side was determined from the obtained BJH plot, and this pore diameter peak was defined as the average pore diameter B of the porous composite material.
[0083] <Maximum Sound Absorption Coefficient on the Low Frequency Side> Using the porous composite materials obtained in Examples and Comparative Examples, the sound absorption coefficient with respect to frequency was measured according to ASTM E1050 using a normal incidence sound absorption coefficient measuring apparatus (manufactured by Nihon Onkyo Engineering Co., Ltd., apparatus name: winZacMTX-15). From the obtained graph of sound absorption coefficient versus frequency, the maximum sound absorption coefficient value in the range of 2000 to 5000 Hz was defined as the maximum sound absorption coefficient on the low frequency side.
[0084] (Example 1) <Preparation process> 0.625 g of polymethyl methacrylate (PMMA) as an organic polymer was dissolved in 6 mL of 80 vol% aqueous ethanol solution at 60°C. Then, 0.64 g of tetramethoxysilane (manufactured by Tokyo Ohka Kogyo Co., Ltd.) as a polysiloxane precursor was added to the resulting solution to obtain a homogeneous solution (homogeneous phase).
[0085] <Precipitate formation process> To the homogeneous solution obtained in the preparation step, 0.354 mL of 1.73 M aqueous ammonia (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (equivalent to 6.1 mmol of ammonia) was gradually added, and the mixture was left to stand for 10 minutes after the addition was complete (condensation step). Next, 0.40 g of trimethoxymethylsilane (manufactured by Tokyo Ohka Kogyo Co., Ltd.) was added to the standing solution as a hydrophobic agent (hydrophobication step). Then, the solution after the addition of the hydrophobic agent was cooled at -20°C for 15 minutes to obtain a wet precipitate (precipitation step).
[0086] <Washing process> The precipitate obtained in the precipitate formation process was washed with ethanol at -20°C.
[0087] <Solvent replacement process> Using n-heptane at -20°C, the solvent of the precipitate after the washing step was replaced from ethanol to heptane.
[0088] <Drying process> The precipitate after the solvent replacement step was dried at room temperature to obtain a porous composite material. Using the obtained porous composite material, the polysiloxane particle content, apparent density, average pore size A and specific surface area A by mercury intrusion method, specific surface area B by BET method, average pore size B by BJT method, and maximum sound absorption coefficient at low frequencies were measured. The results are shown in Table 1. Furthermore, when the obtained porous composite material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0089] (Example 2) Except for changing the amount of tetramethoxysilane used as a polysiloxane precursor from 0.64 g to 1.10 g in the preparation step, and changing the amount of trimethoxymethylsilane used as a hydrophobic agent from 0.40 g to 0.69 g in the precipitate formation step, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1. Furthermore, when the obtained porous composite material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0090] (Example 3) Except for changing the amount of tetramethoxysilane used as a polysiloxane precursor from 0.64 g to 1.50 g in the preparation step, and changing the amount of trimethoxymethylsilane used as a hydrophobic agent from 0.40 g to 0.94 g in the precipitate formation step, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1. Furthermore, when the obtained porous composite material was examined using a scanning electron microscope (SEM), it was found that the porous resin had a structure of interconnected pores, and the silica xerogel had a structure in which polysiloxane particles were linked together in a pearl necklace-like manner, with the silica xerogel present within the interconnected pores of the porous resin.
[0091] (Comparative Example 1) Except for not adding tetramethoxysilane in the preparation step and not performing the condensation and hydrophobicization steps in the precipitate formation step, various operations and measurements were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0092] Note that in Table 1, "PMMA" stands for polymethyl methacrylate. "TMA" stands for tetramethoxysilane. "(CH3O)3SiCH3" represents trimethoxymethylsilane. "Organic polymer / polysiloxane precursor (mass ratio)" indicates the mass ratio of the organic polymer to the polysiloxane precursor. "Hydrophobic agent / Polysiloxane precursor (mass ratio)" indicates the mass ratio of the hydrophobic agent to the polysiloxane precursor.
[0093] [Table 1]
[0094] As is clear from Table 1, the porous composite materials of Examples 1-3 exhibit excellent sound absorption at low frequencies, as evidenced by their high maximum sound absorption coefficient at low frequencies. [Industrial applicability]
[0095] According to the present invention, a porous composite material with excellent sound absorption properties on the low-frequency side can be provided. Furthermore, according to the present invention, it is possible to provide a method for manufacturing a porous composite material that exhibits excellent sound absorption on the low-frequency side.
Claims
1. A porous composite material comprising silica xerogel and porous resin, The silica xerogel contains polysiloxane particles, The average pore size A obtained by the mercury intrusion method is between 5.0 μm and 35.0 μm. A porous composite material having an average pore size B determined by the BJH method of 5.0 nm or more and 30.0 nm or less.
2. The porous resin has a structure of interconnected holes, The silica xerogel has a structure in which the polysiloxane particles are linked together in a pearl necklace-like manner. The porous composite material according to claim 1, wherein the silica xerogel is present in the interconnected pores of the porous resin.
3. The porous composite material according to claim 1, wherein the surface of the polysiloxane particles is hydrophobic.
4. The porous composite material according to claim 1, wherein the content ratio of the polysiloxane particles in the porous composite material is 50% by mass or more and 85% by mass or less.
5. The porous composite material according to any one of claims 1 to 4, wherein the porous resin is composed of a poly(meth)acrylate alkyl ester or a nitrile group-containing polymer.
6. A method for producing a porous composite material comprising silica xerogel and porous resin, A preparation step involves preparing a homogeneous phase containing an organic solvent, a polysiloxane precursor, an organic polymer, and water. The aforementioned homogeneous phase, A condensation hydrophobicization step in which part or all of the polysiloxane precursor is condensed to form polysiloxane particles, and the surface of the polysiloxane particles is made hydrophobic, and Precipitation step to obtain a porous resin by precipitating the organic polymer by a phase separation method. A precipitate formation step is performed to obtain a precipitate containing the polysiloxane particles and the porous resin, A drying step for drying the precipitate, A method for producing porous composite materials, including [the specified element].
Citation Information
Patent Citations
Porous body, and sound insulation material
JP2019167388A